2011
DOI: 10.1016/j.jfma.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Do indoor environments influence asthma and asthma-related symptoms among adults in homes? A review of the literature

Abstract: This review summarizes the results of epidemiological studies focusing on the detrimental effects of home environmental factors on asthma morbidity in adults. We reviewed the literature on indoor air quality (IAQ), physical and sociodemographic factors, and asthma morbidity in homes, and identified commonly reported asthma, allergic, and respiratory symptoms involving the home environment. Reported IAQ and asthma morbidity data strongly indicated positive associations between indoor air pollution and adverse h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 77 publications
1
30
3
2
Order By: Relevance
“…Our results showed that the prevalence of asthma and asthma-related symptoms among adult residents who kept pets in their houses was higher in winter than in summer, which was consistent with other studies from Ireland [29] and Italy [31]. Although previous studies suggest that exposure to aeroallergens in homes may signifi cantly affect pulmonary health, the underlying mechanisms responsible for the observed health effect s are not well understood [32,33].…”
Section: Indoor Exposure To Petssupporting
confidence: 90%
“…Our results showed that the prevalence of asthma and asthma-related symptoms among adult residents who kept pets in their houses was higher in winter than in summer, which was consistent with other studies from Ireland [29] and Italy [31]. Although previous studies suggest that exposure to aeroallergens in homes may signifi cantly affect pulmonary health, the underlying mechanisms responsible for the observed health effect s are not well understood [32,33].…”
Section: Indoor Exposure To Petssupporting
confidence: 90%
“…Extensive research has been performed to identify changes in environmental determinants in recent decades [3]. Although the exact role of the environment in the development of asthma is largely unknown, strong evidence suggests that environmental factors play a key role in its induction or exacerbation [5,8,9]. Asthma is a heterogeneous disease, and categories such as childhood or adult-onset asthma are increasingly accepted as different phenotypes [10].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, it has been suggested that environmental risk factors play a smaller role in inducing new-onset asthma than host factors [24]. In the indoor environment, exposure to allergens such as dust mites, pets (especially cats and dogs), cockroaches, mice and fungi are important risk factors for the development and exacerbations of allergic asthma [8,9,15,19], and prevention and protective interventions have already been proposed [25,26]. The deleterious role of traffic-related air pollution on adult-onset asthma is less conclusive than in childhood-onset asthma [23].…”
Section: Discussionmentioning
confidence: 99%
“…Por esta razão, muitos fabricantes de polímeros e tintas estão buscando soluções mais efetivas para diminuir a concentração de substâncias poluentes liberadas na atmosfera, os chamados COVs [1,2] . Diversas substâncias são classificadas como COVs e podem ter efeitos de curto e longo prazo na saúde dos seres humanos e dos animais, tais como, irritação dos olhos, reações alérgicas, dores de cabeça, problemas respiratórios, efeitos neurotóxicos, dentre outros [3] . De acordo com a Diretiva 2004/42/CE da União Europeia, são classificados como COVs todos os compostos orgânicos com ponto de ebulição menor ou igual a 250°C [4] .…”
Section: Introductionunclassified